Exploring Account Abstraction in Ethereum: A Deep Dive into Erc-4337 - Kamil KACZYŃSKI; Aleksander WIĄCEK (Communications of International Proceedings, 2024)
Ethereum is a decentralised, censorship-resistant blockchain. It allows users to run decentralised applications and deploy Turing-complete smart contracts. However, the Ethereum blockchain is rather stagnant compared to Bitcoin and its ability to introduce new features to its chain. The Ethereum blockchain, unlike Bitcoin, has an Ethereum Virtual Machine (EVM) built into the chain and lets its users run decentralisation and deploy smart contracts, which fulfils one of the main ideas of blockchain. ERC-4337 introduces the possibility of using classic signature algorithms that are more efficient than ECDSA or multiparty computation and threshold signature schemes that further increase security. It also introduces post-quantum signature schemes in the blockchain. This change also allows the use of aggregators that can utilise Boneh-Lynn-Shacham signature schemes, which have also been used in the Ethereum beacon chain protocol. Also, making most of the in-use smart contracts deployed on the chain compatible with ERC-437 can be challenging as they must be upgraded or, if that is not possible, redeployed with code changes. In general, it can make blockchain interactions user-friendly without losing any of the major Ethereum blockchain principles. It laid the foundation of what Ethereum can become in the future, with Web2 functionality.
Keywords: Ethereum; ERC-4337; blockchain; DeFi.